The Impact of TikTok-Based Nutrition Education on Pregnant Women's Knowledge Level About the First Thousand Days of Life for Stunting Prevention - Devita, Hendri; Rifka Yuliana Rizal; Nirmala Sari; Putri Engla Pasalina (International Health Sciences Journal, 2026)
Stunting is a chronic nutritional problem characterized by a child's height below the standard for their age, impacting physical and cognitive development and future productivity. The WHO (2020) indicated that 149.2 million toddlers worldwide experienced stunting. In Indonesia, the prevalence was 24.4% (2021). Based on the Indonesian Nutritional Status Survey (2022), the prevalence of stunting in West Sumatra reached 25.2%, and in Padang City 3.7%, with the highest rate at Dadok Tunggul Hitam Community Health Center at 13.83%. One contributing factor is the low knowledge of pregnant women about nutrition during the First 1,000 Days of Life (HPK). This study used a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 37 pregnant women selected through a purposive sampling technique at Dadok Tunggul Hitam Community Health Center, Padang City. Data were collected using questionnaires before and after the intervention in the form of a TikTok-based educational video, then analyzed using the Wilcoxon Signed Rank Test. The Wilcoxon test showed a p-value of 0.000 (p < 0.05), indicating a significant effect of TikTok-based education on improving pregnant women's knowledge. In conclusion, TikTok is effective as an innovative and easily accessible health education tool for pregnant women. It is recommended that health workers utilize social media as an alternative educational tool for stunting prevention.